Internalization The Character Value Of Love For The Motherland In Preventing Radicalism In Students At The Islamic University Of Jember - Moch. Afif Anshori; Abd. Muhith; Mas’ud, Mas’ud (International Journal of Education, Vocational and Social Science, 2023)
Internalization the character values ​​of love for the motherland exists to unite differences and the spirit of love for the motherland so that it can unite all groups, be it from different cultures, ethnicities, customs and religions. However, incidents of violence in the name of religion have emerged which often become a phenomenon that appears a lot or is known as radicalism in Indonesia. Responding to this threat, UIJ BEM students, supported by students and also the chancellor, declared the campus anti-radical by saying that this declaration was a form of love for the homeland. To analyze and describelevelinternalization of the character values ​​of loving the motherland in preventing radicalism at the Islamic University of Jember. This study uses a qualitative approach by producing descriptive data in the form of written or spoken words from people and observable behavior about Value Internalization Value of the Character of Love for the Motherland in Preventing Radicalism. The results obtained from this study are the character values ​​of loving the homeland which are manifested in the form of campus institutional rules under the auspices of the Nahdatul Ulama Foundation. The vision and mission of the campus are not only Ahlussunnah Wal Jama'ah An Nahdliyah, but also highly committed to upholding Pancasila and -The 1945 Constitution, Strengthening love for the motherland through PKKBM, seminars and general courses, Application of love for the motherland through ceremonial events such as independence, students' day, national recitation and others, Singing the national anthem and hubbul wathan at every event or activity important, Posting photos of the president, vice president, eagle, and campus vision and mission in every classroom, Declaring UIJ as an anti-radical campus. radical issues to grow and develop. Because everything that is applied and accustomed to on the UIJ campus is contrary to the characteristics or indicators of radicalism.